Impact of slot/pole combination on inter-turn short-circuit current in fault-tolerant permanent magnet machines - Dusek, Jiri; Arumugam, Puvaneswaran; Brunson, C.; Amankwah, Emmanuel K.; Hamiti, Tahar; Gerada, C. (Institute of Electrical and Electronics Engineers, 2015)
This paper investigates the influence of the slot/pole (S/P) combination on inter-turn short-circuit (SC) current in fault-tolerant permanent magnet (FT-PM) machines. A 2-D sub-domain field computational model with multi-objective genetic algorithm is used for the design and performance prediction of the considered FT-PM machines. The electromagnetic losses of machines, including iron, magnet, and winding losses are systematically computed using analytical tools. During the postprocessing stage, a 1-D analysis is employed for turn-turn fault analysis. The method calculates self-and mutual inductances of both the faulty and healthy turns under an SC fault condition with respect to the fault locations, and thus SC fault current, considering its location. Eight FT-PM machines with different S/P combinations are analyzed. Both the performance of the machine during normal operation and induced currents during a turn-turn SC fault are investigated. To evaluate the thermal impact of each S/P combination under an inter-turn fault condition, a thermal analysis is performed using finite element computation. It is shown that low-rotor-pole-number machines have a better fault tolerance capability, while high-rotor-pole-number machines are lighter and provide higher efficiency. Results show that the influence of the S/P selection on inter-turn fault SC current needs to be considered during the design process to balance the efficiency and power density against fault-tolerant criteria of the application at hand.